PROSPECTIVE TEACHERS’ FAMILIARITY AND EXPECTATION TOWARD THE IMPLEMENTATION OF STUDENT-CENTERED ENGLISH LANGUAGE TEACHING METHODS - Arina Shofiya; Nanik Sri Rahayu (Jurnal Bahasa Lingua Scientia, 2025)
The development of science and technology brings some impacts to various aspects of life, mainly English Language Teaching (ELT). . However, there is a shift of paradigm as the effect of modernization in ELT, the students become the main subjects of learning and the teaching methods are more student-centered. The prospective teachers need to understand any changes of teaching theories and make adjustment in their future practices. The present research is intended to answer the following research questions: 1) To what extent are the prospective teachers familiar with student-centered English language teaching methods?, 2) What is the perceived contribution of the student-centered English language teaching methods toward their knowledge development?, 3) What do the prospective teachers expect from the student-centered English language teaching methods? The research employed survey design involving 218 students of the fifth semester. The findings reveal that 1) the students show high familiarity to students-centered ELT methods, 2) the methods contribute to the development of their knowledge by providing theory and practices of student-centered ELT method, and 3) they have high expectation in mastering the theories and practice of student-centered ELT methods.